Al-Qisth Based Agricultural Profit-Sharing in Syirkah Al-Mudharabah - Syahidah Rahmah; Mallongi, Syahrir; Lutfi, Mukhtar; Abdullah, Muhammad Wahyuddin (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This study aims to examine the application of profit-sharing al-qisth-based agriculture in syirkah al-mudharabah in Bone Regency. This type of this study is qualitative descriptive using a phenomenological approach to describe the meaning of welfare for farmers through the implementation of a fair syirkah al-mudharabah contract with the stages of determining the scope of the phenomenon, compiling a list of questions, collecting data, clusters of meaning, describing the essence, and reporting. The source of data in this study is the owner farmer and land management farmers. Methods of data collection using the method observation, interview, documentation, and reference search. Then processing techniques and data analysis is carried out through three stages, namely data reduction, data presentation, and drawing conclusions.The results of this study indicate that the concept of agricultural profit sharing is practiced by farmers in Bone Regency, namely 1/2 if the seeds are borne by the owner or 1/3 if the seeds are borne by the manager. Share the results divided after spending the costs incurred during the contract ongoing, the profit sharing portion of bage dua and bage tellu has been considered fair by each party, this depends on how big the capital contribution is given, namely the party that contributes more capital, the greater the benefits to be gained. As a suggestion from this research, it is expected that the government or Islamic financial institutions can adopt this profit-sharing system as a model to facilitate more equitable agricultural financing and cooperation in rural areas.